Determinants of trends in reported antibiotic use among sick children under five years of age across low-income and middle-income countries in 2005–17: A systematic analysis of user characteristics based on 132 national surveys from 73 countries. (July 2021) - Allwell-Brown, Gbemisola; Hussain-Alkhateeb, Laith; Sewe, Maquins Odhiambo; Kitutu, Freddy Eric; Strömdahl, Susanne; Mårtensson, Andreas; Johansson, Emily White
Highlights: This study analysed 132 national surveys from 73 low-income and middle-income countries (LMICs). The reported antibiotic use for sick children aged <5 years in LMICs rose during 2005–2017. The increase was driven by gains among groups underserved by formal health services. These trends were most prominent in low-income countries and South–East Asia. There is a need for studies on appropriateness of antibiotic use in these settings. Abstract: Objectives: This study aimed to analyze any reported antibiotic use for children aged <5 years with fever, diarrhea or cough with fast or difficult breathing (outcome) from low-income and middle-income countries (LMICs) during 2005–2017 by user characteristics: rural/urban residence, maternal education, household wealth, and healthcare source visited. Methods: Based on 132 demographic and health surveys and multiple indicator cluster surveys from 73 LMICs, the outcome by user characteristics for all country-years was estimated using a hierarchical Bayesian linear regression model. Results: Across LMICs during 2005–2017, the greatest relative increases in the outcome occurred in rural areas, poorest quintiles and least educated populations, particularly in low-income countries and South-East Asia. In low-income countries, rural areas had a 72% relative increase from 17.8% (Uncertainty Interval (UI): 5.2%–44.9%) in 2005 to 30.6% (11.7%–62.1%) in 2017, compared to a 29% relative increase in urban areas from 27.1% (8.7%–58.2%) in 2005 to 34.9% (13.3%–67.3%) in 2017. Despite these increases, the outcome was consistently highest in urban areas, wealthiest quintiles, and populations with the highest maternal education. Conclusion: These estimates suggest that the increasing reported antibiotic use for sick children aged <5 years in LMICs during 2005–2017 was driven by gains among groups often underserved by formal health services.